Inibição do crescimento induzida pela lignificação em plantas de soja (Glycine Max L.) expostas à nanopartículas de óxido de ferro (Y-FE203) - Lopes,Tamires Letícia Cunha (2017)
Plants are constantly exposed to environmental perturbations that limit their growth, and one of these conditions is the exposure and interaction with different nanoparticles that are plenty and continuously discarded into the environment. Hitherto, no study has been carried out evaluating the effects of iron (III) oxide (γ-Fe2O3) NPs on soybean growth and lignin production, as we have proposed herein. Furthermore, and for a comparative purpose, we have submitted soybean plants to iron (III) chloride (FeCl3), the ionic counterpart of element iron. Exposure of plants to γ-Fe2O3 NPs stimulated the activity of cell wall-bound peroxidase (POD) of roots, but inhibited the phenylalanine ammonia lyase (PAL) activity, which can be due to the negative feedback of accumulated phenolic compounds. By contrary, the cell-wall bound POD were inhibited by FeCl3. Both γ-Fe2O3 NPs and FeCl3 increased the lignin content in roots and stems. A significant growth inhibition of stems was noted after γ-Fe2O3 NPs exposure, which was due probably to changes in the lignin monomer composition. In this case, γ-Fe2O3 NPs decreased the content of guaiacyl (G) monomer in roots, but increased it in stems. In turn, FeCl3 increased the contents of p-hydroxyphenyl (H) and syringyl (S) in roots. High content of monomer G in stems caused by γ-Fe2O3 NPs decreased the S:G ratios generating a more highly cross-linked lignin followed by the stiffening of the cell wall and growth inhibition. Contrarily, increase of S:G ratio in the roots of plants submitted to FeCl3 are in agreement with the absence of effects on growth, due to production of a less condensed lignin. In brief, our findings showed that both γ-Fe2O3 NPs and FeCl3 act differently in soybean.